Development of a manual of specifications for canned langka (Arthocarpus Ingtegrifolia) in syrup - Velasquez, Divina A.
The study involves the use of objective and subjective measures in establishing levels and tolerances for evaluating canned langka in syrup so that manual of specifications may be designed. Due to limitations of time, only the Homeco brand of canned langka was studied, employing a standardized procedure for its canning. For this reason, the specifications exclude detailed engineering aspects of the problem. From sensory evaluation results of langka of a trained panel, the descriptive product profile for langka showed that texture, flavor, and color appear to be the critical quality quality attributes, these being significantly correlated with general acceptability of the product. Objective measures for quality aspects of canned langka showed a close relation between raw materials and finished product quality. After processing, the flavor of raw material appeared to have developed from a Brix/acid ratio of 73.68 to 209, on the average for the finished product. Penetrometer readings of 225-240 mm for raw material corresponded to firm texture. On the other hand, after processing, the readings ranged from 225-300 corresponding to tender texture. Based on data gathered, the manual of specifications which included quality control charts, was developed. However, the goodness of the manual can only be tested through time and continuous use. Improved test methods, new ideas, and subsequent productions trials are necessary for some added modifications on the manual for canned langka in syrup.